¿Por qué es crucial la China rural? - Poch-de-Feliu, Rafael (Huarte de San Juan. Geografía e Historia, 2006)
The novelty in China this year is the approval of the programme for an integral reform of the countryside. I wonder whether this programme is not an important “symptom” of a change in the political line, or even, in the long term, of the economic model; a change of “recipe book”. The reason for my question is due to the fact that the peasants are the majority of the country’s population, they will carry on being so for 20 or 30 years, they have always been a determining factor for the course of the country, and now it seems that within the current economic model their future has no solution. All this affects the same essence of the Chinese project, common to Mao Zedong, Deng Xiaoping and their successors. To explain this suspicion, we have to first answer two questions; Firstly-What is happening in China? Secondly- What does the “Chinese miracle” consist of?